'Alienable' Possession in Biakic. (24th August 2021) - Bach, Xavier Cédric Alain
Abstract: Alienable possessive constructions in Biakic stand out with respect to the South Halmahera‐West New Guinea language family to which they belong. This article investigates the origins of the innovative alienable possessive forms in Biakic, which constitutes an example of grammaticalization from predicative to attributive possession. It describes the marking of alienable possession for each of the four Biakic languages, examining the form of the markers, their position with respect to the possessum, and the relative order of possessor and possessed, before examining previous analyses of those markers. Object relative clauses in Biakic are compared with possessive markers, concluding that the possessive markers arose from the grammaticalization of an object relative clause. Finally the remaining problem of possessive markers in Meoswar is examined.